Obsessive Compulsive Disorder (OCD) During the COVID-19 Pandemic - Juliana; Nadya Wulandari Alshanti; Tamara Aulia Fakhrinnisa; Nanda Amalia Ramadhanti; Arya Fadlilah Pradana; Revantoro Artha Dwiprawira; Razita Aulia Azkia; Rafid Rabbani Rizkiawan; Muhammad Hafizh; Avianita Dewi Kusumawardhani; Fanny Gunawan; Manika Putri Kunigara; Junjungan Nimasratu Rahmatsani; Hubah Asyiroh; Derryl Rasad Texaga; Firda Fauziah Hidayat; Gading Yudha Pratama; Aldo Aditya Suprijadi; Tomas Marcelino Adistika Martin; Muhammad Rifqo Hafidzudin Farid; Salma Fadila; Adristi Hanun Naziliah; Putu Laksmi Febriyani; Clarisa Christina Gabriella; As'ad Naufal; Ananda Shafira Dwiyanti; Nabila Rosalina Putri (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: The COVID-19 pandemic, present in Indonesia for 17 months, has significantly impacted mental health, especially in individuals with obsessive-compulsive disorder (OCD). Studies in Europe reported a 17.9% to 60.3% increase in OCD symptom severity. Notably, no research in Indonesia has explored the pandemic's effects on OCD patients. Lockdown measures in Indonesia may exacerbate symptoms, but some OCD patients benefit, finding relief from societal stigmatization and the opportunity to advise others on infection prevention. This review aims to examine the impact of the COVID-19 pandemic on OCD patients in Indonesia and discuss potential management strategies. Methods: We conducted a comprehensive literature search, identifying studies, articles, and reports relevant to the effects of the COVID-19 pandemic on OCD patients in Indonesia. These sources were critically evaluated to provide a comprehensive overview. Results: This review reveals that the pandemic poses unique challenges to OCD patients in Indonesia. Lockdown measures may worsen symptoms, although some patients find relief from societal stigmatization. OCD patients can play a valuable role in advising others on infection prevention. Telemedicine, especially CBT, and medication adherence tools are crucial for effective management. Conclusion: The COVID-19 pandemic affects OCD patients in Indonesia in various ways. It is essential to recognize how lockdown measures impact symptom severity and the opportunities for patients to contribute positively to society. Telemedicine and medication adherence tools are valuable for managing OCD during the pandemic. Addressing the needs of OCD patients and implementing effective strategies for their care during COVID-19 is essential in Indonesia.